Action competence for sustainability instrument base on spirituality for prospective science teacher - Husamah, Husamah; Suwono, Hadi; Nur, Hadi; Sabilah, Fardini (Institute of Advanced Engineering and Science, 2024)
Science teachers are the main actors in developing students’ action competence for sustainability (ACS) in the future. Considering that the majority of teachers and prospective science teachers have a spiritual foundation, the spiritual aspect should be an integral part of the ACS. Therefore, an instrument is needed that can measure the level of ACS that includes aspects of spirituality in it. This study was designed to develop and validate an instrument for prospective science teacher in in the form of action competence for sustainability instrument base on spirituality (ACSIS). The instrument was developed based on previous research findings and focus group discussions involving eleven experts. The factors and internal consistency were examined by involving 634 prospective science teachers in Indonesia. Validity and reliability were tested using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). This study’s results showed 21 questionnaire items (four dimensions) with acceptable internal validity and consistency. The ACSIS is recommended to measure the level of ACS for prospective science teachers, specifically in Indonesia, and countries that have the same characteristics of educational problems and potential.